Upaya Pencegahan dan Penanggulangan Kekerasan Seksual Dalam Lingkup Pendidikan Tinggi Universitas Halu Oleo - Amin Tunda; Rety Reka Merlins; Munawir Makmur (Universitas Halu Oleo (UHO), 2025)
The purpose of this study is to find out the efforts to prevent and overcome sexual violence within the scope of higher education at Halu Oleo University, Kendari. Several cases of sexual violence that have occurred within the scope of the Halu Oleo University campus are the reason for conducting this research. Many studies on sexual violence have been carried out, but efforts to prevent and overcome it within the university have never been carried out. This is the basis for why this study was conducted. The research method is carried out with a qualitative approach to dig up information in depth or in-depth interviews with deliberately determined informants who know and understand very well what the object of the research is. The results of the study show that efforts to prevent and overcome sexual violence within the scope of higher education at Halu Oleo University are by forming a task force for the prevention and handling of sexual violence or the Halu Oleo University PPKS Task Force, Kendari. After the task force was formed, the task force sought to conduct socialization and learning activities to introduce an understanding of the types and forms of sexual violence to students, staff, and education staff. The implication of this study is to provide information and knowledge to the public about sexual violence and how to prevent and deal with it.